Meningkatkan Hasil Belajar Siswa Melalui Metode Latihan Terbimbing Pada Mata Pelajaran IPS di Kelas V SD Negeri 1 Ayong - Lantong, Denarti; Oentoe, Fientje J. A.; Mottoh, Yulmi H. (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to determine the improvement in social studies learning outcomes through the Guided Practice Method for class V students at SD Negeri 1 Ayong. This type of research is Classroom Action Research which was carried out over 2 cycles. Each research cycle consists of 4 (four) stages, namely planning, action implementation, observation and reflection with the aim of comparing the values before action and after action. The techniques used for data collection are observation, test and documentation techniques. The research instrument uses test sheets and observation sheets. The data analysis technique used is the percentage calculation data analysis technique. The research subjects were 13 fifth grade students at SD Negeri 1 Ayong. There was an increase in learning outcomes by using the guided practice method on social interaction and human interaction with the environment for class V students at SD Negeri 1 Ayong. The research results showed that in cycle I the average score was 68.84 and the classical completion level was 46.15%. In cycle II, the average score was 95 and the classical completion level was 100%. So it can be concluded that the guided practice method can improve social studies learning outcomes for class V students at SD Negeri 1 Ayong.s.